2006
DOI: 10.1051/0004-6361:20065179
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation of galaxies in the core of the Shapley concentration – the cluster Abell 3558

Abstract: We present an analysis of the spatial orientations of 323 galaxies in the cluster Abell 3558. Our aim is to examine non-random effects in galaxy orientations in the subsample of the cluster. The "position angle-inclination" method is used to find the threedimensional rotation axes. To check for anisotropy or isotropy we carried out three statistical tests: Fourier, Kolmogorov-Smirnov, and Kuiper-V. We assumed a spatially isotropic distribution to examine non-random effects. The galaxies found in the investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Direct galaxy alignments have been detected for some clusters (Plionis et al 2003; but not in others (Strazzullo et al 2005;Aryal, Kandel & Saurer 2006). It is likely that the alignments depend on mass, cluster age and position in complex ways.…”
Section: Introductionmentioning
confidence: 99%
“…Direct galaxy alignments have been detected for some clusters (Plionis et al 2003; but not in others (Strazzullo et al 2005;Aryal, Kandel & Saurer 2006). It is likely that the alignments depend on mass, cluster age and position in complex ways.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ‘hierarchy model’ (Peebles 1969) the directions of the rotation axes should be distributed randomly. Authors have drawn different conclusions regarding these scenarios: (1) no preferred alignment (Helou & Salpeter 1982; Bukhari & Cram 2003; Aryal & Saurer 2005c), (2) tend to orient parallel (Jaaniste & Saar 1978; Flin & Godlowski 1986; Godlowski 1993, 1994; Godlowski, Baier & MacGillivray 1998; Flin 2001) or perpendicular (Reinhardt & Roberts 1972; Gregory, Thompson & Tifft 1981; MacGillivray et al 1982; Baier, Godlowski & MacGillivray 2003) with respect to the cluster [or local supercluster (LSC)] plane, (3) bimodal tendency (Kashikawa & Okamura 1992), (4) local anisotropy (Djorgovski 1983; Flin 1995; Aryal & Saurer 2004, 2005a, 2006; Aryal, Kandel & Saurer 2006), (5) global anisotropy (Parnovsky, Karachentsev & Karachentseva 1994), etc. Godlowski & Ostrowski (1999) noticed a strong systematic effect, generated by the process of deprojection of a galactic axis from its optical image.…”
Section: Introductionmentioning
confidence: 99%
“…Independently, the same method was used to investigate the relationship between the arrangement of the orientation of galaxies and their morphological type according to the Bautz-Morgan classification (BM) and the dispersion of the velocity of galaxies in clusters. In particular, in the work of [98] it was found, contrary to the suggestion of Aryal and Saurer (2004, 2005b, 2005c, 2006, Aryal, Pudel and Saurer (2007) [123,228,233,236,237] that the alignment of the orientation of galaxies is weakly correlated with their morphological type according to the Bautz-Morgan classification (BM). The correlation suggested by Plionis et al (2003) [238] between the degree of alignment of galaxy orientation and the dispersion of galaxies in clusters has also not been confirmed.…”
Section: Studying the Orientation Of Galaxies In Structuresmentioning
confidence: 84%
“…This work showed that the main causes of their occurrence were contamination of the samples by background objects and difficulties in correct interpretation of the results obtained, due to the use of the equatorial coordinate system instead of the Supergalactic system. The importance of choosing the right coordinate system was also pointed out by Flin (1994) [120], Godłowski (1995) [121], Bukhari and Cram (2003) [122], Wu (2006) [107], and especially Aryal, Kandel and Saurer (2006) [123], who showed that the interpretation of the results of studies on the orientation of galaxies in the core of the Shapley Concentration -the cluster Abell 3558 -depends on the coordinate system used. It is also worth noting the results of the work of Kapranidis and Sullivian (1983) [119] who analyzed, in the equatorial coordinate system, the density of the position of the poles of galaxies in regions of size 30 0 x30 0 for a sample of spiral galaxies.…”
Section: Studying the Orientation Of Galaxies At Different Scalesmentioning
confidence: 99%
See 1 more Smart Citation